PERMOHONAN HAK GUNA BANGUNAN ATAS TANAH NEGARA BEKAS EIGENDOM VERPONDING DI KANTOR PERTANAHAN KOTA JAKARTA BARAT - Frando Pranata Sihombing; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2021)
In the control of the former eigendom verponding after the enactment of the Basic Agrarian Law it becomes state land, therefore an application for state land must be made, in this case the application is submitted by the applicant to the state for a certificate of building use rights in accordance with the provisions of the legislation. rights from the land of the former State eigendom verponding at the West Jakarta Land Office and there are obstacles that occur in processing the application. The type of research used in this paper is normative research. To support this research, the author uses a type of literature study, namely reviewing several documents related to this research. The method used is a normative method with a statutory approach. The research data shows how to apply for a right to use a building on state land and there are obstacles in applying for a right to build on state land at the West Jakarta City Land Office.